Accelerating the competitiveness of organic food MSMEs through appropriate technology innovation in Magelang - Orbawati, Eny Boedi; Saleh, Arif Rahman; Puspitasari, Herlina Mega; Fadlurrahman, Fadlurrahman; Mukti, Ari; Ikhtiara, Seiren (Community Empowerment, 2025)
Organic rice and processed vegetable products are flagship commodities in Magelang Regency, yet their development is hindered by limited production capacity and conventional marketing management. This community empowerment program aims to strengthen the competitiveness of two MSME partners through technological innovation and management modernization. The methodology employed a community-based empowerment approach involving technology transfer (vacuum machines, food dehydrators, and stainless-steel grinders), quality management training (Good Manufacturing Practices and HACCP), and digital marketing literacy. The results demonstrated a production capacity increase of 100%, work efficiency improvements of 40%, and a turnover growth of approximately 10%. Furthermore, the partners successfully adopted semi-digital management systems and expanded their market reach through digital marketplaces. These achievements prove that the integration of appropriate technology and digital strategies can effectively transform traditional MSMEs into competitive enterprises with global quality standards.